The New Encyclopaedia Britannica in 30 Volumes (Vol.7) : Macropaedia - Encyclopaedia Britannica, inc. (Chicago Encyclopaedia Britannica, 1982)
The unique four-part organisation of Encyclopaedia Britannica caters for any age and makes it the ideal encyclopaedia for quick, basic information or for an overview of major fields of study. This is the first print edition published since 1998.
Include Tables, Illustration and Graphs
Keywords: Encyclopedias and dictionaries